2015
DOI: 10.1097/sla.0000000000001454
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Margin Width and Recurrence of Ductal Carcinoma In Situ

Abstract: Structured abstract Objective Our goal was to investigate, in a large population of women with DCIS and long follow-up, the relationship between margin width and recurrence, controlling for other characteristics. Summary Background Data While DCIS has minimal mortality, recurrence rates after breast-conserving surgery (BCS) are significant, and half are invasive. Positive margins are associated with increased risk of local recurrence, but there is no consensus regarding optimal negative margin width. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 39 publications
3
39
0
2
Order By: Relevance
“…We have previously reported adjuvant therapy use among larger cohorts of patients with DCIS treated at our institution, with utilization of radiation therapy in recent years for women with DCIS following BCS at approximately 60%, and the use of endocrine therapy substantially lower, at approximately 23%, with no patients receiving chemotherapy. 15-17 Similar utilization of adjuvant therapy for patients with DCIS has been reported from national database reviews. According to National Cancer Institute Surveillance Epidemiology and End Results (SEER) data, approximately 35%–40% of women managed with BCS for DCIS in 2005 did not receive adjuvant radiation therapy 18 , and in a review of over 206,000 women with DCIS reported to the National Cancer Database between 2005 and 2012, the minority of women (37%) received adjuvant endocrine therapy.…”
Section: Discussionmentioning
confidence: 55%
“…We have previously reported adjuvant therapy use among larger cohorts of patients with DCIS treated at our institution, with utilization of radiation therapy in recent years for women with DCIS following BCS at approximately 60%, and the use of endocrine therapy substantially lower, at approximately 23%, with no patients receiving chemotherapy. 15-17 Similar utilization of adjuvant therapy for patients with DCIS has been reported from national database reviews. According to National Cancer Institute Surveillance Epidemiology and End Results (SEER) data, approximately 35%–40% of women managed with BCS for DCIS in 2005 did not receive adjuvant radiation therapy 18 , and in a review of over 206,000 women with DCIS reported to the National Cancer Database between 2005 and 2012, the minority of women (37%) received adjuvant endocrine therapy.…”
Section: Discussionmentioning
confidence: 55%
“…Due to heterogeneity in margin definitions across studies, positive margins were re-categorized as either 0mm (ink on tumour, nine studies 19-27 ) or <1mm (seven studies 28-34 ). In addition, margins of <2mm (three studies 18;35;36 ) or <3mm (one study 37 ) were considered positive when 0mm or <1mm were not reported.…”
Section: Methodsmentioning
confidence: 99%
“…One margin distance could be included for each study. When multiple distances were available, the largest was chosen (with the exception of the only study to apply a 5mm distance 19 , and a large study defining “close” margins as <2mm 27 ). The effect of alternative distance categorisations for potentially influential studies was investigated.…”
Section: Methodsmentioning
confidence: 99%
“…After adjustment for multiple factors, margin width was a more highly significant predictor of IBTR (p < 0.0001). 22 The MP felt that, overall, the heterogeneity of the evidence between the above-reported studies did not allow for a definitive recommendation for margin widths greater than 2 mm in patients foregoing RT.…”
Section: Guideline Recommendationsmentioning
confidence: 99%
“…The conclusion that re-excision could be selectively employed with margins smaller than 2 mm was influenced by the high long-term rates of local control reported in the NSABP DCIS trials which required a margin of no ink on tumor 7 as well as the study of Van Zee et al which, after adjusting for multiple covariates, found no difference in risk between margins of ≤ 2 mm and more widely clear margins in patients receiving WBRT. 22 …”
Section: Guideline Recommendationsmentioning
confidence: 99%